IRE1α overexpression in malignant cells limits tumor progression by inducing an anti-cancer immune response. (31st December 2022) - Martinez-Turtos, Adriana; Paul, Rachel; Grima-Reyes, Manuel; Issaoui, Hussein; Krug, Adrien; Mhaidly, Rana; Bossowski, Jozef P.; Chiche, Johanna; Marchetti, Sandrine; Verhoeyen, Els; Chevet, Eric; Ricci, Jean-Ehrland
ABSTRACT: IRE1α is one of the three ER transmembrane transducers of the Unfolded Protein Response (UPR) activated under endoplasmic reticulum (ER) stress. IRE1α activation has a dual role in cancer as it may be either pro- or anti-tumoral depending on the studied models. Here, we describe the discovery that exogenous expression of IRE1α, resulting in IRE1α auto-activation, did not affect cancer cell proliferation in vitro but resulted in a tumor-suppressive phenotype in syngeneic immunocompetent mice. We found that exogenous expression of IRE1α in murine colorectal and Lewis lung carcinoma cells impaired tumor growth when syngeneic tumor cells were subcutaneously implanted in immunocompetent mice but not in immunodeficient mice. Mechanistically, the in vivo tumor-suppressive effect of overexpressing IRE1α in tumor cells was associated with IRE1α RNAse activity driving both XBP1 mRNA splicing and regulated IRE1-dependent decay of RNA (RIDD). We showed that the tumor-suppressive phenotype upon IRE1α overexpression was characterized by the induction of apoptosis in tumor cells along with an enhanced adaptive anti-cancer immunosurveillance. Hence, our work indicates that IRE1α overexpression and/or activation in tumor cells can limit tumor growth in immunocompetent mice. This finding might point toward the need of adjusting the use of IRE1α inhibitors in cancer treatments based on the predominant outcome of the RNAse activity of IRE1α.